How do you use the rational roots theorem to find all possible zeros of f(x) = 2x^3 + 8x^2 + 7x - 8?

1 Answer
Aug 13, 2016

f(x) has no rational zeros, so use Cardano's method to find Real zero:

x_1 = 1/6(-8+root(3)(-424+54sqrt(58))+root(3)(-424-54sqrt(58)))

and related Complex zeros.

Explanation:

f(x) = 2x^3+8x^2+7x-8

By the rational roots theorem, any rational zeros of f(x) can be expressed in the form p/q for integers p, q with p a divisor of the constant term -8 and q a divisor of the coefficient 2 of the leading term.

That means that the only possible rational zeros are:

+-1/2, +-1, +-2, +-4, +-8

None of these work, so we need other means to find the zeros:

color(white)()
Descriminant

The discriminant Delta of a cubic polynomial in the form ax^3+bx^2+cx+d is given by the formula:

Delta = b^2c^2-4ac^3-4b^3d-27a^2d^2+18abcd

In our example, a=2, b=8, c=7 and d=-8, so we find:

Delta = 3136-2744+16384-6912-16128 = -6264

Since Delta < 0 this cubic has 1 Real zero and 2 non-Real Complex zeros, which are Complex conjugates of one another.

color(white)()
Tschirnhaus transformation

To make the task of solving the cubic simpler, we make the cubic simpler using a linear substitution known as a Tschirnhaus transformation.

0=108f(x)=216x^3+864x^2+756x-864

=(6x+8)^3-66(6x+8)-848

=t^3-66t-848

where t=(6x+8)

color(white)()
Cardano's method

We want to solve:

t^3-66t-848=0

Let t=u+v.

Then:

u^3+v^3+3(uv-22)(u+v)-848=0

Add the constraint v=22/u to eliminate the (u+v) term and get:

u^3+10648/u^3-848=0

Multiply through by u^3 and rearrange slightly to get:

(u^3)^2-848(u^3)+10648=0

Use the quadratic formula to find:

u^3=(848+-sqrt((-848)^2-4(1)(10648)))/(2*1)

=(-848+-sqrt(719104-42592))/2

=(-848+-sqrt(676512))/2

=(-848+-108sqrt(58))/2

=-424+-54sqrt(58)

Since this is Real and the derivation is symmetric in u and v, we can use one of these roots for u^3 and the other for v^3 to find Real root:

t_1=root(3)(-424+54sqrt(58))+root(3)(-424-54sqrt(58))

and related Complex roots:

t_2=omega root(3)(-424+54sqrt(58))+omega^2 root(3)(-424-54sqrt(58))

t_3=omega^2 root(3)(-424+54sqrt(58))+omega root(3)(-424-54sqrt(58))

where omega=-1/2+sqrt(3)/2i is the primitive Complex cube root of 1.

Now x=1/6(-8+t). So the zeros of our original cubic are:

x_1 = 1/6(-8+root(3)(-424+54sqrt(58))+root(3)(-424-54sqrt(58)))

x_2 = 1/6(-8+omega root(3)(-424+54sqrt(58))+omega^2 root(3)(-424-54sqrt(58)))

x_3 = 1/6(-8+omega^2 root(3)(-424+54sqrt(58))+omega root(3)(-424-54sqrt(58)))